Knowledge, attitudes and practices regarding sexual health among Chinese medical students: a multicenter cross-sectional study - Han Yao; Runping Ma; Qiufan Sun; Jinhong Zhao; Yicheng Li; Tianqi Bao; Tao Li (BMC Medical Education)
Abstract Background Sexual health is crucial for overall well-being, yet sexual health education among medical students in China remains limited. This multicenter cross-sectional study assesses the knowledge, attitudes, and practices (KAP) regarding sexual health among Chinese medical students to inform educational policies. Methods An electronic survey was conducted across three leading medical institutions in Beijing, targeting postgraduate medical students. The survey assessed demographics, sexual health knowledge, attitudes, and behaviors. Data were analyzed using descriptive statistics and logistic regression to identify factors associated with sexual behavior. Results Among 765 participants, 79% identified as heterosexual, and 28.2% reported engaging in sexual activity. While the overall sexual health knowledge was relatively high, students with sexual experience had significantly higher contraceptive knowledge. Misconceptions were common, with 25.8% believing that sex during the safe period doesn’t lead to pregnancy, and 14.9% considering withdrawal before ejaculation effective for contraception. Positive attitudes toward sexual health were noted, though traditional views on committed relationships persisted. Logistic regression identified factors associated with sexual activity: higher monthly expenses, rural residency, and non-heterosexual orientation. Undergraduate and female students were less likely to engage in sexual activity. Conclusions This study highlights significant gaps in sexual health knowledge, particularly about contraception and HPV vaccination. The findings stress the need for comprehensive sexual health education to address knowledge gaps and cultural attitudes, preparing future healthcare professionals for effective, non-judgmental patient care.